Development of the distribution of wealth in Iceland 1997-2017 - Katrín Svava Másdóttir 1995- (2019)
Inequality exists in every economy. Economist Thomas Malthus believed that inequality within societies are inescapable (Piketty, 2014). Iceland is no exception to the general structure of wealth inequality within advanced economies (AEs). In this thesis the distribution of wealth between 1997-2017 in Iceland is analyzed focusing on what are the main drivers of wealth inequality and how has the distribution of wealth changed during these twenty years especially following the 2008 financial crisis. To analyze the development of wealth distribution a principal component analysis is performed as well as comparing net wealth between percentiles. In Iceland, between 1997-2017 the top 1% wealthiest individuals of the population owned more than half of total net wealth and in 2010 that percentage increased to over 70% of total net wealth. Wealth inequality reached its high point in 2010, then decreased yearly but in recent years has risen again. Between 1997 and 2007, the years before the financial crisis, the cause of wealth inequality was mostly due to the fact that the lower percentiles did not own any assets and most had negative net wealth. Following the financial crisis their net worth decreased significantly, with the bottom 10% reaching a negative net worth of more than nine million ISK in 2010. Since 2010 the lower percentiles have increased their net worth yearly although the bottom 10% have not yet reached a positive net worth in 2017. The difference between total assets of the lower percentiles, i.e. bottom 30% of the population, compared to the top 1% has decreased since 2010. Yet the difference between total assets of the middle percentiles compared to the top 1%, has gradually increased since 2010. The analysis in this thesis of the distribution of wealth in Iceland concludes that wealth inequality rose during the years prior to the financial crisis, reached its high point in 2010 and then decreased again. Yet what is also interesting from the analysis is that the structure of wealth inequality during the ...